2009
DOI: 10.1088/0953-8984/21/34/344207
|View full text |Cite
|
Sign up to set email alerts
|

A high-magnetic-field-induced density-wave state in graphite

Abstract: Whilst the realization of graphene, probably one of the best two-dimensional carrier systems to study, has attracted much research interest recently, graphite, which may be regarded as multi-layered graphene, has also been known to exhibit very interesting phenomena at high magnetic fields and low temperatures. The electron-hole system in the compensated semimetal graphite undergoes a magnetic-field-induced electronic phase transition and successive transitions, including a reentrant transition back to the nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
45
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 28 publications
4
45
1
Order By: Relevance
“…Figure 2 shows the in-plane resistance of the graphite crystal for fields up to 60 T and temperatures below 10 K. The in-plane resistance first increases steeply, superimposed by Shubnikov-de Haas oscillations, and saturates above 15 T due to the presence of a closed Fermi surface [7,22,50,51]. At lowest temperatures a step is observed in the in-plane resistance at around 30 T, followed by a steep increase of the resistance, reaching its maximum value at 48 T before it drops down to below its initial value at around 53 T. This behavior has already been reported for Kish and highly oriented pyrolytic graphite, and has been attributed to the formation of a DW state [12,22,27,33,52]. Similar features can also be identified in the out-of-plane transport [12,35].…”
supporting
confidence: 69%
See 1 more Smart Citation
“…Figure 2 shows the in-plane resistance of the graphite crystal for fields up to 60 T and temperatures below 10 K. The in-plane resistance first increases steeply, superimposed by Shubnikov-de Haas oscillations, and saturates above 15 T due to the presence of a closed Fermi surface [7,22,50,51]. At lowest temperatures a step is observed in the in-plane resistance at around 30 T, followed by a steep increase of the resistance, reaching its maximum value at 48 T before it drops down to below its initial value at around 53 T. This behavior has already been reported for Kish and highly oriented pyrolytic graphite, and has been attributed to the formation of a DW state [12,22,27,33,52]. Similar features can also be identified in the out-of-plane transport [12,35].…”
supporting
confidence: 69%
“…Improved LL calculations by Takada and Goto [25] showed that electron correlations play a crucial role in renormalizing the Slonczewski-Weiss-McClure LL structure. Subsequent experiments to higher fields [26,27] identified a transition at 52 T corresponding to the collapse of a density wave phase as the (0; ↑) or (−1; ↓) LL emptied. So far attempts to directly measure the gap of this putative density wave spectroscopically [28,29] Recently, Fauqué et al [12] discovered the onset of a second density-wave anomaly above 53 T, by out-of-plane transport measurements on Kish graphite up to 80 T. This state was found to collapse at 75 T into a state with metallic c-axis conductivity.…”
mentioning
confidence: 99%
“…This paper is devoted to Emanuil Aizikovich Kaner with whom we wrote two works on the oscillations in 2D coherent MB structures [26,27]. We have predicted in [27] a cascade of the magnetic-breakdown structural Pierls-like phase transitions which is similar to recent observations in graphite [7,49].…”
Section: F S εsupporting
confidence: 66%
“…The critical temperature increases proportionally to the MB probability ( ) W B together with the bandwidth 0 exp ( / ). [7,49].…”
Section: Discussionmentioning
confidence: 99%
“…This destruction was attributed to the depopulation of a Landau sub-level within the framework of YF scenario. The possible multiplicity of induced phases and their signatures in the in-plane and out of-plane charge transport remain open questions (for a review see [18]). Therefore, despite a large body of research on graphite at high magnetic field, the nature of its electronic ground state is not settled.…”
mentioning
confidence: 99%